FOLK GAMES SERVES AS A PSYCHOSOCIAL DEVICE - Mekhri Norbosheva Achilovna (Scholar Express Journal, 2022)
This article folk games psychology is strengthened. The problem of enriching the psychological foundations of a child’s personality development through his play activities is increasingly occupying the minds of his followers. The clear application of this direction in the theory of psychology and pedagogical practice is already yielding tangible results
Keywords: Folk games; psychology; child